Effect of complete bed rest duration on vascular complication after angiography ‎in hospitalized patients in post angiography units in health centers in Rasht - rabiolah farmanbar; maryam guozliyan; mojgan Baghaie; moohamad taghi moghadamniya; majid chinikar; zahra atrkarruoshan (Journal of Holistic Nursing and Midwifery)
Introduction: Coronary artery angiography is an important diagnostic method in patients with ‎coronary disease which like other diagnostic methods has side effects. The important ‎complication of it is vascular side effects (hematoma and bleeding) in place of sheet insertion. ‎In order to control it, one must be in complete bed rest (CBR) and in no reference an exact ‎time is mentioned for it.